PREPOSISI DALAM DRAMA AWAY KARYA MICHAEL GOW - SEBA, VIRKA ANGELINA S (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This research entitled ‘‘Preposition in Drama Away by Michael Gow’’ is written to analyze and classify the form and the meaning of the preposition that are use in drama. A preposition is a word that connects a noun or pronoun with a verb, adjective, or another noun or pronoun by indicating a relationship between the things for which they stand. In analyzing the data, the writer used Quirk Randolph and Harman’s theory, and the data were taken from the Drama Away by Michael Gow. The problems of this research are focused on what are the from and the meaning of preposition. The forms are simple preposition and complex preposition. The meanings of preposition refer to the apposition, cause or reason, comparison, concession, condition, degree, description, direction, design, instrument, manner, material, means, measure, objective genitive, partition, place, purpose, quality, respect, source, time, and value.   Key words: English Preposition, Forms and Meaning, Drama Away by Michael Gow